2009
DOI: 10.1111/j.1747-0765.2009.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater contribution of low-nutrient tolerance to sorghum and maize growth under combined stress conditions with high aluminum and low nutrients in solution culture simulating the nutrient status of tropical acid soils

Abstract: Aluminum is usually regarded as the determining factor for plant growth in acid soils and nutrient deficiencies are often additional growth‐limiting factors in tropical acid soils. Taking into account the potential interactions between Al toxicity and nutrient deficiencies, the present study investigated sorghum (Sorghum bicolor Moench [L.]) and maize (Zea mays L.) cultivar differences for: (1) Al tolerance (relative growth in a one‐fifth strength nutrient solution [low‐nutrient medium, ionic strength: 4.5 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“… Khan et al (2009) reported that Al tolerance was positively correlated with the ratio of sterols to phospholipids in root-tip cells of various rice cultivars. Application of uniconazole-P, an inhibitor of obtusifoliol-14α-demethylase (OBT 14DM), decreased the sterol content in root-tip cells of rice.…”
Section: Introductionmentioning
confidence: 99%
“… Khan et al (2009) reported that Al tolerance was positively correlated with the ratio of sterols to phospholipids in root-tip cells of various rice cultivars. Application of uniconazole-P, an inhibitor of obtusifoliol-14α-demethylase (OBT 14DM), decreased the sterol content in root-tip cells of rice.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that mineral stress resulting from either deficiencies in mineral nutrients and/or toxicity of excessive minerals may play an important role in our understanding how global climate change will affect plants in real world soils (Lynch and St.Clair ; Akhter et al. ). However, the majority of research on the effect of elevated [CO 2 ] on plant growth has mainly focused on the interaction between elevated [CO 2 ] and the mineral nutrients essential for plant growth and development so far, whereas a few studies have examined the responsiveness of plant growth to [CO 2 ] enrichment in the presence of toxic metals in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Similares resultados encontraron Rengel y Robinson (1989). Por otro lado, Akhter et al (2009) señalan que en un experimento con sorgo en solución nutritiva, los resultados indicaron que entre las menos tolerantes al Al, la mayor tolerancia estaba dada por una menor absorción de Al en las raíces. Marín-Garza et al (2010), señalan que en un experimento con arroz en solución nutritiva, las concentraciones de Al en la parte aérea aumentaron en relación al aumento de la concentración de Al en solución.…”
Section: Materiales Y Métodosunclassified